FAKTOR-FAKTOR YANG MEMPENGARUHI PROGRAM GERAKAN MEMBANGUN PRODUKSI TERNAK BERORIENTASI AGRIBISNIS (GEMPITA) TERHADAP KINERJA GEMPITA DI KABUPATEN JEMBRANA - Bayu Putri, Francisca Sagita Hendrayani; Utama, Made Suyana; Urmila Dewi, Made Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
Poverty can not be separated from national strategies for achieving development. The vision and mission of livestock development in Jembrana is the realization of advanced breeding, efficient, tough and independent towards a prosperous Jembrana through Movement Building Livestock Production Oriented Sustainability (euphoria). This study aims to analyze; 1) influence management organization to the empowerment of livestock groups, 2) effect of management organization and empowerment of livestock on the performance program euphoria, 3) monitoring and evaluation moderating influence management organization and empowerment of livestock on the performance program euphoria, 4) whether the empowerment of livestock group mediating the influence of the organization program management on the performance of euphoria in the district of Jembrana. The research data sources used, there are two primary data obtained from interviews to goat and secondary data obtained from the Animal Husbandry in Jembrana. The research data collection methods used were in-depth interviews and questionnaires, with a number of respondents as many as 80 people. The analysis tool used is Test Validity and Reliability Instruments and structural equation analysis (SEM) with alternative Partial Least Square (PLS-based component SEM).
Keywords: Movement Building Livestock Production Oriented Sustainability (euphoria), organizational management, empowerment, monitoring and evaluation, performance